2011
DOI: 10.1007/s10535-011-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

A two-step protocol for shoot regeneration from hypocotyl explants of oilseed rape and its application for Agrobacterium-mediated transformation

Abstract: A two-step protocol for improving the frequency of shoot regeneration from oilseed rape (Brassica napus L.) hypocotyl explants was established. The protocol consists of a pre-culture on callus induction medium (CIM) and a subsequent shoot regeneration on shoot induction medium (SIM). The SIM was Murashige and Skoog medium supplemented with different concentrations of 6-benzylaminopurine (BA; 2 -5 mg dm -3 ) and naphthaleneacetic acid (NAA; 0.05 -0.15 mg dm -3 ). Maximum frequency of shoot regeneration (13 %) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Cotyledonary node explants infected for 15 min obtained the highest transformation efficiency in this study. In contrast to this result, Mashayekhi et al (2008), Khan et al (2010) and Tang et al (2011) reported that 5-10 min of infection showed the maximum transformation efficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Cotyledonary node explants infected for 15 min obtained the highest transformation efficiency in this study. In contrast to this result, Mashayekhi et al (2008), Khan et al (2010) and Tang et al (2011) reported that 5-10 min of infection showed the maximum transformation efficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Silver thiosulphate, an ethylene inhibitor, is often used to block the action of this hormone. Application of this compound has been shown to increase the stable transformation efficiency of black cherry (Liu and Pijut 2010) and oilseed rape (Tang et al 2011). Similarly, the presence of STS in selection media used for chestnut somatic embryos improved the transformation efficiency, although differences were not significant.…”
Section: Discussionmentioning
confidence: 97%
“…Brassica carinata A. Br. (Yang et al, 1991), Arabidosis thaliana (Gendreau et al, 1997), Brassica napus L. (Tang et al, 2011), Brassica oleracea cv. (Gambhir et al, 2017) Zygophyllum potaninii (Bayarmaa et al, 2018), Solanum quitoense (Gutiérrez et al, 2019).…”
Section: Direct Organogenesismentioning
confidence: 99%